Debunking leadership sayings III: avoiding the pitfalls of a clean sweep. (2nd May 2019) - Ellis, Peter; Abbott, Jane
Abstract : In this paper, Peter Ellis and Jane Abbott explore some more of the issues with a new management attempting a clean sweep and changing too much, too fast. They offer some practical advice to avoid the perils of losing the organisation's memory by attempting to sweep clean when this may not be necessary